Nonlinear models for recognition of concentration of mixture - Ivanauskas, Feliksas; Paulauskas, Robertas; Vaitkus , Pranas (Lietuvos matematikos rinkinys, 2021)
In this paper extreme learning machine and support vector regression are used for biosensors response to mixtures of compounds classification. The results are compared with the results obtained using artificial neural networks and others.